MEMBANGUN KESADARAN SISWA TERHADAP LINGKUNGAN MELALUI SOSIALISASI GAYA HIDUP ZERO WASTE DI SDN CITAPEN - Audina, Mia; Awaliyah, Fitri; Nur Pika, Yuni; Sri Wulan, Widya; Maigita Lusiana, Ega; Nur Malasari, Mala; Rhamdini, Sita; Pradana, Aji; Purnawansyah, Reza (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM Azramedia Indonesia, 2024)
The waste problem is an increasingly pressing issue in various regions, including in villages. Citapen Village is one of the villages in Japara District, Kuningan Regency, West Java, which is still facing environmental health problems. Citapen Village is faced with an increasingly worrying waste problem. This is due to the lack of public understanding regarding the importance of waste management. To overcome this, the Real Work Lecture (KKN) Students of the Muhammadiyah University of Kuningan held a Zero Waste program. This program was implemented on July 30, 2024 at Citapen Elementary School. In its implementation, students used the Socialization method in the room by introducing the concept of the 5R movement consisting of Refuse (refuse), Reduce (reduce), Reuse (reuse), Recycle (recycle) and Rotting (rot). This activity was attended by all students and homeroom teachers of grade 4 of Citapen Elementary School. The results obtained through this activity were that students could understand and know how to implement a zero waste lifestyle.